Deportasi Massal TKI dari Malaysia : Ancaman Baru bagi Keamanan Perbatasan Indonesia - Hanif Tamam Zuhair (Mandub : Jurnal Politik, Sosial, Hukum dan Humaniora, 2025)
The mass deportation of Indonesian migrant workers (TKI) from Malaysia is a multidimensional threat to national security, especially in Indonesia's border areas. In 2022–2023, more than 40,000 migrant workers were forcibly repatriated, mostly through North Kalimantan and Riau. Malaysia's strict immigration policies such as Operation Nyah and the implementation of online recruitment procedures accelerate the deportation process and increase migrant workers' vulnerability to exploitation. This journal examines the impact of these deportations on local socio-economic stability, increased cross-border crime, and institutional weaknesses in the management of migrant worker repatriation and reintegration. Using a policy study approach and analysis of deportation data, the paper highlights the need for integrated and responsive security policies and strengthened bilateral Indonesia–Malaysia coordination. Recommendations focus on institutional capacity building, protection of migrant workers' rights, and a human security approach in dealing with the challenges of forced migration.